MEDIA PEMBELAJARAN SKETCHUP 3D MATA PELAJARAN KONSTRUKSI DAN UTILITAS GEDUNG JURUSAN DPIB - Jumadil Ali; Revian Body (Jurnal Applied Science in Civil Engineering, 2021)
This research departs from the low scores of students in the subject of Construction and Building Utilities, besides that there is no media that is attractive and easy to understand, due to time and conditions that have not made it possible to make the required media. The purpose of this study (1) to find out what the appropriate 3D visual-based building construction drawing media looks like using the 3D SketchUp program (2) to produce learning media products for teachers that are attractive and easy to understand by students, in the form of 3D visual-based learning media using the SketchUp 3D program. Using research and development methods (Design and Development Research). The development model used is in the form of developing a learning system with the ADDIE model. ADDIE stands for Analysis, Design, Development or Production, Implementation or Delivery and Evaluations. Of the five stages in this research, only three stages will be carried out, starting from (1) the analysis process followed by (2) the design process to (3) the development process. The results of the study were in the form of learning media for building construction images. This learning media with the Module file format (.skp), learning media files can be run with the 3D SketchUp application. The learning media will be packaged in a Compact Disk (CD), which contains two learning media files. (1) File 1 contains drawings of unreinforced building construction, (2) File 2 contains detailed drawings of building construction reinforcement.